Literature Review: Students' Mathematical Understanding in Solving Problems on Ratio and Scale - Sjahrawi, Wilda Fakhira; Darmawan, Puguh; Rofiki, Imam (Rafandha Press, 2024)
This research aims to conduct a literature review on students' mathematical understanding ability in solving problems on ratio and scale material at the junior high school level and to understand the importance of mathematical understanding for students in the learning process so that students are able to solve mathematical problems and are able to see the importance of students' mathematical understanding in everyday life. The method used in the research is a literature review of various indexed sources with the source of the study in the form of students' mathematical understanding in mathematics learning. It is necessary to teach ratios to students with a high level of mathematical understanding in addition to forcing them to memorize formulas. Moreover, as a means of promoting good comprehension during the learning process, students receive additional, varied practice questions. In order to further encourage students to improve their mathematical grasp of ratio content, teachers should also play a role in encouraging a type of early appreciation in the development of students' mathematical understanding and by giving them several opportunities to review and fix errors.